A statistical assessment of demographic bonus towards poverty alleviation - Jamal Abdul Nasir; M. H. Tahir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
The shift of birth and death rates from high to low level in any population is referred as demographic transition. Mechanically, the transition of a society creates more working member of its own population commonly called demographic bonus. This article empirically explores the realistic soundness of demographic bonus in reducing the poverty level of the society. Three contrasting regions namely Eastern Asia, Central America and Oceania were selected for analytical purposes. The findings indicate that Eastern Asia and Oceania are currently facing the end of their transition whereas the Central America is lagged behind in transition. Central America due to last runner in transition race is the sustained recipient of its own demographic bonus by the year 2030. On the basis of three mechanisms namely: labour supply, savings and human capital, the Eastern Asian region is found to be successful beneficiary of its own demographic gift which concludes that many million people have escaped from poverty. Under the right policy environment on the above three mechanisms, Eastern Asia experience indicates the realistic contribution of demographic bonus to reduce poverty.
Keywords: 330; Demographic bonus; demographic transition; human capital; labour supply; savings